Design, synthesis, and bio-evaluation of new isoindoline-1,3-dione derivatives as possible inhibitors of acetylcholinesterase - Motahareh Hassanzadeh; Farshid Hassanzadeh; Ghadam Ali khodarahmi; Mahbobe Rostami; Fateme Azimi; Hamid Nadri; Farshad Homayouni Moghadam (Wolters Kluwer Medknow Publications, 2021)
Background and purpose: Alzheimer's disease is considered one of the lead causes of elderly death around the world. A significant decrease in acetylcholine level in the brain is common in most patients with Alzheimer's disease, therefore acetylcholinesterase (AChE) inhibitors such as donepezil and rivastigmine are widely used for patients with limited therapeutic results and major side effects. Experimental approach: A series of isoindoline-1,3-dione -N-benzyl pyridinium hybrids were designed, synthesized and evaluated as anti-Alzheimer agents with cholinesterase inhibitory activities. The structure of the compounds were confirmed by various methods of analysis such as HNMR, CNMR, and FT-IR. Molecular modeling studies were also performed to identify the possible interactions between neprilysin and synthesized compounds. Findings/Results: The biological screening results indicated that all synthesized compounds displayed potent inhibitory activity with IC50 values ranging from 2.1 to 7.4 μM. Among synthesized compounds, para-fluoro substituted compounds 7a and 7f exhibited the highest inhibitory potency against AChE (IC50 = 2.1 μM). Molecular modeling studies indicated that the most potent compounds were able to interact with both catalytic and peripheral active sites of the enzyme. Also, some of the most potent compounds (7a, 7c, and 7f) demonstrated a neuroprotective effect against H2O2-induced cell death in PC12 neurons. Conclusion and implications: The synthesized compounds demonstrated moderate to good AChE inhibitory effect with results higher than rivastigmine.